Hubungan Motivasi dan Minat dengan Hasil Praktik Kewirausahaan Siswa Kelas XI Tata Boga di SMK Dharma Wanita Gresik - Rizky Nova Prasetya; Sri Handajani; Niken Purwidiani; Mein Kharnolis (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This study aims to determine: 1) the relationship of motivation to the results of entrepreneurial practices of class XI Culinary students at SMK Dharma Wanita Gresik; 2) the relationship between interest in entrepreneurship and the results of entrepreneurship practices of class XI Culinary Class students at SMK Dharma Wanita Gresik; 3) the relationship between motivation and interest in entrepreneurship on the results of entrepreneurial practices of class XI Culinary students at SMK Dharma Wanita Gresik. This research is a descriptive research with a quantitative approach. The population in this study were 35 students of class XI Culinary at Dharma Wanita Gresik Vocational School. Research data was collected through questionnaires and observation. Data analysis was carried out by product moment correlation analysis and multiple correlation with the help of SPSS 22 for windows software. The results of the study show that: 1) there is no positive and significant relationship between motivation and the results of entrepreneurial practices for students of Class XI Culinary at SMK Dharma Wanita Gresik. Evidenced by the value of r-count < r-table, namely (0.151 <0.334); 2) there is no positive and significant relationship between the interest in entrepreneurship and the results of entrepreneurial practices of Class XI Culinary Class students at SMK Dharma Wanita Gresik. Evidenced by the value of r-count < r-table, namely (0.171 <0.334); and 3) there is no positive and significant relationship between motivation and interest in entrepreneurship on the results of entrepreneurial practices of Class XI Culinary Class students at SMK Dharma Wanita Gresik. Evidenced by the value of r-count < r-table, namely (0.172 <0.334). The R value (correlation coefficient) is 0.172, so it can be concluded that the level of relationship between variables X1 and X2 to Y simultaneously has a very low relationship.